Digynic triploidy: utility and challenges of noninvasive prenatal testing. Issue 6 (9th April 2015) - Fleischer, Julie; Shenoy, Archana; Goetzinger, Katherine; Cottrell, Catherine E.; Baldridge, Dustin; White, Frances V.; Shinawi, Marwan
Key Clinical Message Low fraction fetal DNA in noninvasive prenatal testing in the context of fetal growth restriction and multiple congenital anomalies should alert medical professionals to the possibility of digynic triploidy. Single‐nucleotide polymorphism microarray can detect the parental origin of triploidy and explain its mechanism.